The cerebellum in Alzheimer's disease: evaluating its role in cognitive decline - Jacobs, Heidi I L; Hopkins, David A; Mayrhofer, Helen C; Bruner, Emiliano; van Leeuwen, Fred W; Raaijmakers, Wijnand; Schmahmann, Jeremy D (Brain (London, England : 1878), 2018)
The cerebellum has long been regarded as essential only for the coordination of voluntary motor activity and motor learning. Anatomical, clinical and neuroimaging studies have led to a paradigm shift in the understanding of the cerebellar role in nervous system function, demonstrating that the cerebellum appears integral also to the modulation of cognition and emotion. The search to understand the cerebellar contribution to cognitive processing has increased interest in exploring the role of the cerebellum in neurodegenerative and neuropsychiatric disorders. Principal among these is Alzheimer's disease. Here we review an already sizeable existing literature on the neuropathological, structural and functional neuroimaging studies of the cerebellum in Alzheimer's disease. We consider these observations in the light of the cognitive deficits that characterize Alzheimer's disease and in so doing we introduce a new perspective on its pathophysiology and manifestations. We propose an integrative hypothesis that there is a cerebellar contribution to the cognitive and neuropsychiatric deficits in Alzheimer's disease. We draw on the dysmetria of thought theory to suggest that this cerebellar component manifests as deficits in modulation of the neurobehavioural deficits. We provide suggestions for future studies to investigate this hypothesis and, ultimately, to establish a comprehensive, causal clinicopathological disease model.